The impact of green skills on green behavior and performance in green HR management at vocational training institutions - Setiawan, Andre; Aida, Neli; Ribhan; Banuwa, Laili Fadhila; Mariska, Mega; Shafira, Nabilla (Lighthouse Publishing, 2025)
This research aims to analyze the implementation of green human resources management and its influence on green skills on green behavior and impanct to performance. This research data is cross sectional and was collected only once, through distributing an online questionnaire on Google Form using a Likert scale of up to 5 points, from strongly disagree to strongly agree. The research sample was taken using purpose sampling which resulted in 100 samples at the Vocational Training Institute. This research uses instrument tests in the form of validity tests, reliability tests and data analysis techniques with Smart PLS. According to the research's findings, implementing green human resources management has a positive impact on both green skills and green behavior. Green skills also have a positive impact on behavior because they encourage employees to voice their opinions or ask other employees to do the same on environmentally friendly issues. in order to enhance green behavior and skills. In the future, this study can help managers understand how they might support green behavior in their firms by focusing on employee dedication, contribution, and voice.